Measuring Connotative Meaning in English Translations of the Holy Qur'an: A Semantic and Applied Analysis - Ali Albashir Mohammed Alhaj (QiST: Journal of Quran and Tafseer Studies, 2026)
In a systematic semantic and applied analysis, this study investigates the transfer of connotative meaning in the English translations of the meanings of the Holy Qur'an. Instead of applying an instrument that treats Qur'anic connotation in isolation as subjective or impressionistic, the research introduces and operates a three-level gradational measurement instrument (weak, moderate, and strong) to measure the strength with which translations preserve rhetorical power, symbolic complexity, and pragmatic aim. Employing a qualitative descriptive-analytical approach, the study employs semantic analysis, rhetorical analysis, as well as contextual-pragmatic interpretation, to compare verses in selected Qur'anic texts with their English translations. This study reveals that comparatively weak connotative transfer frequently corresponds with literal, denotative translation styles in which speakers use surface lexical matching of expressions while minimizing imagery and discourse-level connotative meaning. Meaningfully, moderate transfer is partial success in communicating emotional or imagistic impact, while strong transfer reflects the symbolic, doctrinal, and ideological impact of the Qur'anic text by interpreting based on knowledgeable decision making. The study thus establishes and demonstrates the extent to which Qur'anic connotative meaning can be extracted and disentangled from subjective interpretation judgments, and that analysis for interpretation is a method of tackling this problem, which is currently an inadequate area of translation studies in Qur'an. The results provide a theoretically-grounded foundation for translation studies that enables comparison in translation work and provide an empirical basis for translators, researchers, and educators dealing with semantic fidelity and pragmatic adequacy during translation of sacred texts as they practice their profession.